A distributed SCTP scheme for bandwidth aggregation - Elahi, Mohammad Mamun; Khan, Shahin (16th Int'l Conf. Computer and Information Technology, 2014)
Bandwidth aggregation is a popular research topic that enables users to use different kind of network interfaces connected with Internet together. This is very useful especially in modern smart phones, where multiple interfaces can be used not only to aggregate bandwidth, but also to use an uninterrupted network connection. For different reasons, service providers may not be able to provide service all places according to customers' need. Also, Line may be dropped for mobility. Considering all those factors, we have developed an algorithm that extends basic Stream Control Transmission Protocol (SCTP) to aggregate bandwidths of multiple interfaces. In this paper, we have simulated the effects of different related parameters using C programming language and measured and demonstrated performance of the suggested algorithm graphically.